THE USE OF ORAL PRESENTATION IN TEACHING ENGLISH TO IMPROVE STUDENTS SPEAKING SKILL - Ati, Asih; Parmawati, Aseptiana (PROJECT (Professional Journal of English Education), 2022)
Speaking is an ability that is considered quite important in learning English. The oral presentation is one activity that can be used in learning English to improve students' speaking skills. This study aims to examine the oral presentations conducted by students with the intention that students can improve their speaking also seeks to determine what obstacles students experience when making oral presentations. The researcher applied qualitative research as a research method to collect the data the researcher used observation and field notes as instruments. The data obtained were categorized and analyzed based on several related theories. Regarding the result, it was found that basically, students have a positive response to the implementation of oral presentation. Student perceives that it helps them to evaluate their ability to speak English, increasing motivation, as well as allowing them to think critically in the use of language. Although several aspects must be developed such as student pronunciation. This finding indicates that oral presentations are useful for improving students speaking skills. Keywords:  Oral Presentation, Speaking Skill